The words and expressions used by debaters in arabic language debates: a systematic review of previous studies - Abu Bakar, Radhwa; Abu Bakar, Nur Hadirah Hanim (Al-Qanatir International Journal of Islamic Studies, 2025)
The lack of proficiency in words and expressions is one of the reasons for the failure of debaters in Arabic debates. It is even worse when a debater does not know or master the basic vocabulary and expressions related to the issue. Therefore, this research aims to identify the precise and fundamental words and terms used by competent Arab debaters in debates, so that other debaters can benefit from and refer to them. To achieve this, the research will answer the question: What are the words and expressions used by competent Arab debaters in Arabic language debates? To clarify this, the researchers adopted the systematic review methodology of previous studies using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method, which revealed 428 articles related to the study topic based on two databases: Google Scholar and EBSCO Discovery Service (EDS). After examination, the research concluded that only 8 articles were selected and appropriate for the topic. Additionally, many words and expressions used by debaters in Arabic debates were identifiedsuch as "Allow me, in this joyful session, to present the various arguments from our side” and “From the government's side, as we firmly stand by our position today, which is that raising the oil prices subsidy is necessary in view of the goal of this project."However, there are some linguistic errors in the use of these words and expressions. Therefore, the researchers proposed several suggestions for future studies to address this linguistic issue.